Computer-Aided Design and Analysis of the Farthing System for a Substation in an Industrial Zone: a Real Case Study - Tutus, Emir Kaan; Kumru, Celal Fadil; Ates, Yavuz; Partal, Ertugrul (IEEE, 2024)
Design of high-voltage substation earthing is crucial for operational security, human safety, equipment protection, and the earth potential rise impact on third-party installations. However, an earthing system without detailed design and not compliant with regulations may fail to provide the desired level of protection during faults and lightning. In particular, the earthing system's complex geometry and the nonuniform soil structure suggest that empirical formulas based on assumptions cannot provide accurate and detailed designs. In this regard, using software for earthing calculations and analyzing key parameters affecting the design is essential for the accuracy and appropriateness of the design. Therefore, in this study, the earthing system design of a substation is conducted using XGSLab Software. The impact of soil resistivity and ground return current on the zone of influence is analyzed, and the critical touch voltage level of the designed system is determined. Furthermore, the results obtained using XGSLab Software are compared and assessed against conventional calculation methods. The results reveal that the magnitude of the ground return current and the soil resistivity significantly affect the zone of influence and touch voltage. Moreover, it is determined that the use of software with high analysis capacity, rather than conventional empirical formulas, leads to more precise and consistent results in calculation and analysis processes in earthing system designs.
Keywords: Earthing system design; zone of influence; transferred voltage; XGSLab; TSO earthing system specifications; Energy & Fuels; Engineering